Defective Leptotene Chromosome 1 (DLC1) encodes a type‐B response regulator and is required for rice meiosis. (14th May 2019) - Tao, Yang; Chen, Dan; Zou, Ting; Zeng, Jing; Gao, Fengyan; He, Zhongshan; Zhou, Dan; He, Zhiyuan; Yuan, Guoqiang; Liu, Miaomiao; Zhao, Hongfeng; Deng, Qiming; et al.
Summary: Meiosis is critical for sexual reproduction and the generation of new allelic variations in most eukaryotes. In this study, we report the isolation of a meiotic gene, DLC1, using a map‐based cloning strategy. The dlc1 mutant is sterile in both male and female gametophytes due to an earlier defect in the leptotene chromosome and subsequent abnormalities at later stages. DLC1 is strongly expressed in the pollen mother cells (PMCs) and tapetum and encodes a nucleus‐located rice type‐B response regulator (RR) with transcriptional activity. Further investigations showed that DLC1 interacts with all five putative rice histidine phosphotransfer proteins (HPs) in yeast and planta cells, suggesting a possible participation of the two‐component signalling systems (TCS) in rice meiosis. Our results demonstrated that DLC1 is required for rice meiosis and fertility, providing useful information for the role of TCS in rice meiosis. Significance Statement: As a member of the two‐component signalling system (TCS), DLC1 participates in rice meiosis and is required for leptotene chromosome organization and fertility.